Improving Student Learning Outcomes By Using Blended Learning Assisted Pizzaku Media (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2022)
The purpose of this classroom action research was to determine the success of blended learning using pizzaku media. The key data sources in this study were 17 male and 15 female students from class VIA SD Negeri Bujanggadung, Grogol District, Cilegon City, Banten. According to the study's findings, using face-to-face and online synchronous blended learning methods using the Google Meet application and pizzaku media might boost the learning interest of class VIA students at SDN Bujanggadung in studying mathematics, particularly in the circle content.